Biofuel from algae ? photobiological hydrogen production and CO2-fixation. (7th August 2007) - Mullner, Katrin; Happe, Thomas
The reduction of CO2-emissions that are damaging our climate is one of the major challenges of contemporary energy management. Nature itself offers us possibilities to produce energy CO2-neutrally with the help of hydrogen producing micro-algae. Under certain conditions the light energy collected by photosynthesis is used to transfer electrons to hydrogen producing proteins called hydrogenases. A new type of hydrogenase that produces molecular hydrogen with high rates was isolated (Happe and Naber, 1993) and characterised on genomic level (Happe and Kaminski, 2002) for the first time in green algae. Processes were recently developed that allow a long-term production of hydrogen by micro-algae (Melis et al., 2000). Under sulphur deprivation the green alga Chlamydomonas reinhardtii adapts its metabolism from oxygen production and CO2-fixation towards hydrogen production. Therefore the biotechnological process is divided into the growth, the hydrogen production and the utilisation and treatment of the available energy in the form of hydrogen and biomass.